THE CONCEPTUALITY AND DENOTATIVENESS OF SPACE IN THE ANOMALOUS WORLD OF FANTASY - Diana Valeryevna Abduramanova (European Science Publishing, 2024)
The article examines the additive and constitutive features of the fantasy genre in the projection of the creation of denotations of the communicative space of the anomalous world, forming a special language of communication between the fictional characters of the work. During the study, certain aspects of the definition of the anomalous world put forward in the works of some literary critics were challenged.
Keywords: mythological sign, denotation, concept, fantasy, anomaly, world.